Seaweed-eating sheep and the adaptation of husbandry in Neolithic Orkney: new insights from Skara Brae. (August 2019) - Balasse, Marie; Tresset, Anne; Obein, Gaël; Fiorillo, Denis; Gandois, Henri
Abstract: Abstract : The Neolithisation of Europe involved socio-economic and biological adaptations to new environments. The use of seaweed as livestock fodder, for example, was key to the introduction of animal husbandry to the Orkney archipelago, c. 3500 cal BC. Using stable isotope analysis of faunal remains from Skara Brae, this study provides new evidence for, and clarifies the chronology of, the adoption of seaweed consumption by sheep. The results show that sheep consumed moderate amounts of seaweed from the moment of their introduction to Orkney—a practice that facilitated the successful spread of the farming lifeways to the most remote areas of Europe.